2010
DOI: 10.1002/sia.3692
|View full text |Cite
|
Sign up to set email alerts
|

One‐step electrodeposition of amorphous carbon films containing WO3 with high conductivity and good wettability

Abstract: Tungsten trioxide-incorporated hydrogenated amorphous carbon (WO 3 /a-C : H) films have been fabricated on a single-crystal silicon wafer by liquid phase electrodeposition using methanol as carbon source and tungsten carbonyl as incorporated reagent. The morphology, composition and structure of the films have been investigated by SEM, XPS, Raman scattering spectroscopy, Fourier transform infrared spectroscopy (FTIR) and Transmission electron microscope (TEM), respectively. The effects of WO 3 incorporation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…as antifuses . Correspondingly, there are numerous successful attempts in synthesizing a‐C film, including vapor deposition and liquid deposition . According to the similarity of many physical properties and microstructures to those of either graphite or diamond, a‐C films are usually divided into diamond‐like carbon films and graphite‐like carbon (GLC) films .…”
Section: Introductionmentioning
confidence: 99%
“…as antifuses . Correspondingly, there are numerous successful attempts in synthesizing a‐C film, including vapor deposition and liquid deposition . According to the similarity of many physical properties and microstructures to those of either graphite or diamond, a‐C films are usually divided into diamond‐like carbon films and graphite‐like carbon (GLC) films .…”
Section: Introductionmentioning
confidence: 99%
“…Analytical pure methanol (99.5%) was used as carbon source and the concentration of tungsten carbonyl which used as an incorporated reagent was 0.2 mg/ml. The films deposition was carried out under an applied voltage of 1200 V and ambient temperature of 55 ± 2°C for 8 h [11]. Recently, tungsten trioxide (WO 3 ) and molybdenum trioxide (MoO 3 ) nanoparticles (DLC nanocomposite coatings) has been incorporated into DLC by first uniformly dispersing these nanoparticles into isopropanol solution and incorporated into DLC coatings deposited on a tappet valve (metallic substrate) deposition parameters for DLC-MoO 3 and DLC-WO 3 coatings is shown in Table 1 [12,13].…”
Section: Nanoparticles Incorporated Dlc Coatingsmentioning
confidence: 99%
“…Recently, the incorporation of nanoparticles into DLC has been used by first dispersing the nanoparticles into hexane or isopropanol, thereafter, introducing the dispersed nanoparticles into the reactor chamber through the nanoparticle inlet, this deposition method has been described by some authors in literature [7][8][9][10][11][12][13]. These nanoparticles which have been used includes Ag [7], TiO 2 [8][9][10], WO 3 [11,12] and MoO 3 [13]. In this chapter the use of diamond-like carbon coatings for automobile engine applications, due to their ultra-low friction coefficient and Diamond-Like Carbon (DLC) Coatings for Automobile Applications DOI: http://dx.doi.org/10.5772/intechopen.95063 excellent wear resistance will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] The WO 3 -TiO 2 nanocomposite is an energy storage photocatalyst, which can store electrons generated under light, and release these electrons in the absence of light, which occurs in electron-mediated reactions. 44,45 For instance, Yang et al 41 used a WO 3Àx /TiO 2 lm as a new photoanode which reduced CO 2 to form formic acid through photocatalysis. Wang et al 42 found that the prepared WO 3 /TiO 2 nanotube composite lm showed a signicant increase in the degradation rate of volatile organic compounds under a photocatalytic degradation process.…”
Section: Introductionmentioning
confidence: 99%